Field evaluation of early vigour for genetic improvement of grain yield in wheat - Botwright, T.L.; Condon, A.G.; Rebetzke, G.J.; Richards, R.A. (Commonwealth Scientific and Industrial Research Organisation, 2002)
Improved early vigour in wheat (Triticum aestivum L.) has been proposed as an important trait for increasing grain yield through greater water-use efficiency in rainfed, Mediterranean-type environments. Three years of field trials were undertaken in Western Australia at 2 sites, Merredin (low rainfall, 244 mm in the growing season) and Wongan Hills (medium rainfall, 308 mm), to examine the influence of increased early vigour on crop growth and yield. The effect of breeding for greater early vigour was tested in 1998 and 1999 using 3 high vigour and 3 low vigour BC2:F5 lines of the cultivar Amery backcrossed to a 'high vigour' donor. Averaged across environments, the high vigour backcross lines had a 10% increase in early vigour (i.e. leaf area/plant) at 50 DAS compared with the low vigour lines. Differences in yield across environments were associated with variation in total rainfall, rainfall distribution, and soil properties. In the wetter of the 2 years (1999), greater early vigour translated to increased yield of c. 12%, averaged across environments, but there was no difference in yield in either environment in the drier year (1998). Potential deleterious effects of the recurrent parent on yield were eliminated in field trials in 1999 and 2000 by manipulating early vigour through varying grain size (25, 35, or 50 mg) or seeding density (50, 200, or 400 plants/m2) of Amery at sowing. Large grain increased the embryo size and early vigour at 50 DAS in both environments in 1999. This translated to greater biomass production at anthesis and maturity to increase grain yield at Wongan Hills in 1999. In contrast, there was no relationship between grain size, biomass production, and yield at Merredin in 1999 or at either site in 2000. Sowing density treatments also had no effect on yield in 2000. In conclusion, there is potential to increase yield of wheat by selecting for greater early vigour in a wheat breeding program. The expression of vigour in field conditions and the translation of this improvement to higher yields is, however, dependent on the environment. Current yield limitations arising through backcrossing with a high vigour, yet poor yielding donor, need to be addressed.